Effects of Total Sulfur Amino Acids on Growth Performance, Immunity, and Meat Yield in Broilers Fed Diets With and Without Antibiotics - Adhikari, Pratima Acharya; Castro, Fernanda Lima de Souza; Liu, Guanchen; Kim, Woo Kyun (Frontiers in Veterinary Science, 2022)
Two experiments were conducted to evaluate effects of sulfur amino acids (SAA) on performance, carcass yield, immunity, and amino acid transporters in broilers fed diets with/without an antibiotic growth promoter (AGP). In Experiment 1, a total of 250 one-day old Cobb500 male chicks were assigned to battery cages with two levels of AGP (0 and 0.05% Bacitracin) and five levels of SAA (0.7, 0.8, 0.9, 1.0 and 1.1%) for 21d. In Experiment 2, a total of 900 one-day old chicks were assigned to floor pens with two levels of AGP and three levels of SAA for starter (0.7, 0.8 and 0.9%) or finisher phase (0.52, 0.62 and 0.72%) for 42d. In experiment 1, from 0-7d, the body weight gain (BWG) was the lowest for birds fed 0.7% SAA. AGP significantly decreased the feed conversion ratio (FCR), and birds fed 0.9 and 1.1% SAA had significantly lower FCR than 0.7% SAA. From 8-14d, for AGP fed birds, the lowest BWG was observed in 0.7% SAA group. In birds not fed AGP, birds fed 0.8% SAA had higher BWG than 0.7 and 1.1% SAA. Birds fed 0.7% SAA diet had lower feed intake (FI) than 0.8% SAA and higher FCR than 0.8, 0.9, and 1.0% SAA. In experiment 2, from 0-21d, the lowest BWG and highest FCR were observed in birds fed 0.7% SAA, whereas birds fed 0.9% SAA had highest BWG and lowest FCR. From 22-42d, FCR was lower for birds fed AGP, and for birds fed 0.72%. Interactions between the factors were found for FI and BWG. The whole thigh and wing weights were the highest for 0.62% SAA, and the Pectoralis Major weight was higher for birds fed 0.62% SAA than those fed 0.52% SAA. There was an interaction between SAA and AGP for Lat1 (large neutral amino acid transporter), and AGP fed birds had higher expression of interleukin 1β (Il-1β). Interleukin 10 (Il-10) was upregulated in the ileum. There was an interaction between the factors for sodium-dependent neutral amino acid transporter B(0)AT1 (SLC6A19) expression. The results suggested that AGP and SAA supplementation would affect growth performance of broilers.